Evaluasi Indeks Urban Pada Citra Landsat Multitemporal Dalam Ekstraksi Kepadatan Bangunan - - Sukrisyanti (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2007)
ABSTRACT The information of building density is so necessary in city planning. Monitoring ofthe dynamic city changing can be helped by the remote sensing data, one of them is Landsat image. Supposed to Kawamura (1997), urban index (UI) transformation on Landsat can be used to extract the building density. Application of a transformation is not enough to be adopted only, but it has to be evaluated, in order to increase the transformation accuracy. This research is done to evaluate the UI transformation on Landsat TM (Thematic Mapper) and ETM+ (Enhanced Thematic Mapper plus) images in extracting the density building. The digital image processing of multitemporal images has been done to reach the goal. We used ‘inner ringroad Yogyakarta’ as a research area. This research has got a summary that the UI transformation will be effective if it be applied in built up area only. If the area is a mixture of built up and non built up area, it has to be filtered by land cover layer (built up and non built up area).